(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
The article argues the expediency of creating an interactive educational environment for the use of situational-communicative models of professional interaction of future pediatric dentists. In general, the diagnosis and treatment of a child’s dental diseases requires qualified performance of the necessary manipulations by a pediatric dentist. Preventive work with children-patients, preparation of the child-patient for treatment procedures is based on the readiness of the pediatric dentist to create such a communicative environment that will contribute to the establishment of a trusting relationship between the patient and the dentist. Teaching students to create optimal professional communication is possible in the conditions of interactive cooperation. It is argued that in the professional training of future pediatric dentists, it is advisable to focus students’ attention on the need to master the experience of performing several functions (purely professional, psychological, educational, teaching), an important feature of which is the ability to establish professional communication with all participants. Performance of diverse roles in the work of future pediatric dentists requires the approbation of relevant skills and abilities by students in the conditions of a specially created interactive educational environment. The result of involving students in professional communication in an interactive educational environment is the acquisition by future pediatric dentists of the necessary experience in organizing effective professional interaction. Each of the participants of the situational-communicative models of professional interaction of future pediatric dentists is able to determine the goals and prospects of personal professional development in the context of testing and choosing appropriate forms and methods of professional communication. It is summarized that in the process of creating an interactive educational environment using situational and communicative models of professional interaction, it is necessary to consider various aspects that indicate the development of a new system of training future pediatric dentists.